KNOW: Knowledge in Action for Urban Equality - Castán Broto, Vanessa (2023)
This working paper serves as the basis for a critical examination of the notion of knowledge co-production. The paper examines how the idea of knowledge co-production has emerged in relation to the parallel but distinct concept of service co-production and the participatory development planning tradition. It also examines the variety of processes of knowledge co-production that may take place in the context of academic research.In doing so, the working paper highlights the centrality of knowledge co-production in the Knowledge in Action for Urban Equality (KNOW) project’s research strategy, with a focus on actionable knowledge that may support transformative trajectories towards urban equality. Such an approach is based on the view that knowledge production underpins the process, ethics, and outcomes of any urban development intervention. Using well-documented examples of knowledge co-production in urban equity research, the article discusses how co-production is carried out in practice. Focusing on how co-production is used in active research also helps to identify some key constraints and challenges, as well as existing mechanisms for overcoming them. This discussion leads to a proposed research agenda on knowledge co-production in the context of the KNOW project.